The Rural-Urban Interface in the Global South: Planning and Governance Challenges - Christian M. Rogerson (African Journal of Hospitality, Tourism and Leisure, 2023)
The urban periphery in the Global South is a zone experiencing rapid and dynamic processes of change. The rural-urban interface is where urban and rural areas meet with the production of peri-urban spaces. These areas confront unique and acute problems and require distinctive innovative planning approaches and solutions to their complex challenges. As recreation and the tourism and hospitality sector can be critical components in peri-urban spaces it is essential that tourism scholars appreciate the broad changes occurring in these areas and their multiple challenges for planning and governance. This article provides a review of existing debates about peri-urban spaces in the Global South focused on their planning and governance challenges.